Proceso de intervención psicológica para fortalecer la relación madre-hijo desde la perspectiva de apego seguro en madres adolescentes de 15 a 17 años del centro de ADOLE-ISIS fundación patronato municipal San José en el período abril-julio de 2015 - Bayas Velastegui, Katherine Alexandra (2016)
This report systematizes the intervention from secure attachment perspective, which was carried out with adolescent mothers of ADOLE-ISIS Center and her children, and that included two axes: work in individual psychotherapy sessions and strengthening the link through early stimulation sessions. It also describes the initial situation of attachment and the changes that occurred, all of which were recorded by adapting the experiment "strange situation" proposed by Mary Ainsworth and carried out both at the beginning and end of the intervention. The need of process is justified by the psychosocial status and the vulnerability of people with whom it worked, also briefly recount the particular circumstances of each case and the progress achieved or not in each one of them. Theoretically underpinned by Bowlby deepens into the importance of secure attachment, its influence on the development of the child's psyche and the impact on future social relations, while supported by Ainsworth's theory, the types of attachment observed in praxis are defined and categorized. Finally conclusions and recommendations are made, regarding the intervention carried out, their mistakes, successes, achievements and results.